Investigation of piezoelectricity in perovskite (LaFeO3): A theoretical study - dos Santos, C. C.; Barbosa, J. P.; dos Santos, M. A. B.; Lira, F. A. M.; Cardoso, F. J. B.; Pinheiro, J. C.; Treu Filho, O.; Kondo, R. T. (Elsevier B.V., 2007)
In a previous report we studied theoretically the piezoelectric effect in barium titanate (BaTiO3) [O. Treu Filho, J.C. Pinheiro, R.T. Kondo, J. Mol. Struct. (THEOCHEM), 671 (2004) 71]. In this article we applied the Hartree-Fock (HF) theory in the investigation of piezoelectricity in LaFeO3. Initially, the generator coordinate HF (GCHF) method was used to build 22s14p, 30s19p13d, and 32s24p17d Gaussian basis sets for O(3p), Fe(D-5), and La(D-2) atoms. Then those basis sets were contracted to [7s6p], [13s8p6d], and [18s13p7d], respectively. The quality of the contracted basis sets in polyatomic calculations was evaluated through calculations of total and orbital energies (HOMO and HOMO-1) of (FeO1+)-Fe-2 and (LaO1+)-La-1. Finally, the contracted basis sets were supplemented with polarization and diffuse functions and used to investigate the piezoelectricity in LaFeO3. The calculated properties were dipole moment, total energy, and atomic charges and the analysis of those properties showed that covalent bonds constitute the electronic structure of [LaFCO3](2) fragment. Therefore, it is reasonable to believe that LaFeO3 does not present piezoelectric properties. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: investigation of piezoelectricity; LaFeO3; theoretical study; ab initio study; Gaussian basis sets; GCHF method